1993
DOI: 10.1021/ic00073a014
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation of four-center two-electron bonding involving boron derivatives

Abstract: Factors contributing to the stability of 4c2e bonds have been investigated by means of ab initio calculations on boranes and carboranes. Electron density plots and "deformation energies", the energy required to deform the deprotonated species into a geometry optimal for interacting with the added proton, have been used to help evaluate the propensity of 4c2e vs 3c2e bonding. Two molecules exhibiting 4c2e bonding, CB5H7 (1) and B6H7-(2), have been optimized at MP2/6-31G* with the "extra" hydrogen capping a tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0
3

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 2 publications
4
36
0
3
Order By: Relevance
“…The spatial extents of the orbital and the bond lengths are correlated because the stabilization of the hydrogen atom in these metal clusters results from the in-phase interaction of the atomic orbitals comprised of the 1s orbital of the hydrogen atom and the hybridized s and d orbitals of the metal atoms. This is somewhat akin to the stabilization of hydrogen atoms bound through three-center four-electron ͑3c-4e͒ bonds in boranes, 85 wherein the hydrogen atom is located at the intersection of the three boron p orbitals.…”
Section: B M 13 H N Clustersmentioning
confidence: 99%
“…The spatial extents of the orbital and the bond lengths are correlated because the stabilization of the hydrogen atom in these metal clusters results from the in-phase interaction of the atomic orbitals comprised of the 1s orbital of the hydrogen atom and the hybridized s and d orbitals of the metal atoms. This is somewhat akin to the stabilization of hydrogen atoms bound through three-center four-electron ͑3c-4e͒ bonds in boranes, 85 wherein the hydrogen atom is located at the intersection of the three boron p orbitals.…”
Section: B M 13 H N Clustersmentioning
confidence: 99%
“…[126][127][128][129] However, a later analysis by Mach et al 130 showed that a structure with C s symmetry locates a global minimum that is approximately 25.1 kJ•mol Ϫ1 lower than that of T d . The rotational constants were derived from the structure of Mach et al 130 The vibrational frequencies ͑scaled by 0.943͒ were computed by Carpenter, 131 who also concluded that C s has the lower energy.…”
Section: B 4 Hmentioning
confidence: 99%
“…As its existence is associated with the overlap of the π* orbitals of each fragment, the bonding interaction will be found whenever two [TCNE] − fragments are placed at such a short distance from each other, either because the interaction between these two fragments is energetically stabilizing, or because some external force drives them together. Multicentered two‐electron (including four‐centered) bonding18 has been reported for several boranes,19 and for the structurally constrained, but not structurally characterized 1,3‐dehydro‐5,7‐adamantanediyl20a and pagodane dications;20b however, this is the first example for a carbon‐based system as well as being the first example of a bonding interaction residing over four atoms.…”
Section: Resultsmentioning
confidence: 99%